Negligence in biomedical research: an anti-racist approach for substance use researchers - Lehman, Jonathan; Balangoy, Danniella; Mejia, Angie P.; Cardenas-Iniguez, Carlos; Marek, Scott; Randolph, Anita C. (Frontiers in Public Health, 2024)
Racism is embedded in the fabric of society at structural, disciplinary, hegemonic, and interpersonal levels, working as a mechanism that drives health disparities. In particular, stigmatized views of substance use get entangled with racialization, serving as a tool to uphold oppressive systems. While national health institutions have made commitments to dismantle these systems in the United States, anti-racism has not been integrated into biomedical research practice. The ways in which substance use researchers use and interpret race data—without engaging in structural racism as a mechanism of health inequity—can only be described as inadequate. Drawing upon concepts from the Public Health Critical Race praxis, QuantCrit, and an anti-racism research framework, we recommend a set of guidelines to help biomedical researchers conceptualize and engage with race more responsibly in substance use research.